Evaluasi Kelembagaan Pinjaman Dana Syariah yang Menggunakan Pembiayaan Berbunga Perspektif Fatwa DSN MUI No. 117 Tahun 2018 - Aulia, Dini; Zahara, Fatimah (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Lending institutions in Indonesia have developed digitally, both conventionally and sharia-based. The large number of sharia-based lending platforms means that the MUI must provide provisions for running them which are regulated in the MUI DSN Fatwa No. 117. The formation of sharia lending institutions must follow the provisions set by the MUI. One of the sharia-based loan platforms is PT Dana Syariah. this institution So this article was written with the aim of looking at the Fatwa's views on the interest provisions set by Dana Syariah. This article was written using a juridical-normative research method, namely case study legal research, because the problems studied are in certain institutions and certain laws. This research approach will use a normative juridical approach supported by arguments. The research results show that PT Dana Syariah has violated 1 provision in implementing information technology-based financing services, namely providing 2% interest as an absolute additional form of financing. This must be reviewed by the MUI and OJK in implementing information technology-based financing services.